Naive Bayes-based Visualization of Disease-related Data in Muara Telang Public Health Centers - Yansah, Nopri (PT. Lentera Ilmu Publisher, 2023)
This study addresses the imperative need for active and efficient management of Community Health Centers (Puskesmas) in Indonesia, as mandated by the Minister of Health's Regulation. The role of these centers in managing and planning health development within their work areas is crucial for comprehensive, integrated, acceptable, and affordable health efforts. The utilization of visualization, particularly through computer technology, emerges as a vital tool for conveying complex health data to the public, facilitating quicker understanding and informed decision-making. Focusing on the Sumber Marga Telang Health Center in South Sumatra Province, the research employs a structured waterfall model for system development. The Naive Bayes algorithm is utilized to classify internal and eye diseases, offering a practical solution to the challenge of conveying disease data to the public effectively. In conclusion, this research provides a comprehensive approach to enhancing health information dissemination and data visualization at community health centers, contributing significantly to public awareness and preventive healthcare efforts.